Schistosomiasis and Acute Appendicitis - Figueiredo, Jacinta (2014)
Acute appendicitis associated to Schistosoma haematobium and S. mansoni infection has been found in patients submitted to urgent appendectomy at the Hospital Américo Boavida in Luanda. Due to the high prevalence and morbidity caused by schistosomiasis (or bilharziasis) in the country, we suspect that the involvement of Schistosoma infection on appendicular pathology could be very frequent, in particular for those individuals more exposed to the parasite transmission. We report two clinical cases of acute appendicitis whose surgical specimens of the appendix revealed S. haematobium and S. mansoni eggs in histological samples. The reported patients live in endemic areas and have been exposed to schistosome during childhood, which may explain the infection’s chronicity. Information of these clinical cases could be relevant, particularly for surgery specialists and clinical pathologists, due to the possibility of finding more patients with concurrent appendicitis and schistosomiasis.Keywords: Appendicitis/parasitology; Schistosomiasis; Angola; África.